Perkembangan Sistem Pengemasan Bahan Makanan - Rasyid Hasan (Balai Besar Kimia dan Kemasan, 1983)
The importance of packaging around food has been recognized for centuries. From man's early beginning, use of leaves, gourds shells and animal parts such as blodder's and skin's served as a means of packaging, if only to hold and carry food. Since the nineteenth century, more sophisticated forms of packaging such as tin cans and glass jars have come into use, not only as a means of holding and transporting, but also as a means of preserving it. The purpose of this trends in food packaging to give a letter perspective from bulk handling of the raw commodity to the retail consumer product.